A Snapshot of Australian Network Infrastructure Practice - Dell, Peter; Ding, Ding (Communication Economics and Electronic Markets Research Centre, 2005)
Structured cabling is the network infrastructure embedded within a building's structure, typically within ceilings, walls, and risers between floors. Installation of such infrastructure is costly and disruptive; thus, installing appropriate cable types is especially important. Structured cable often has a lifespan of 15 years or more and the consequences of a poor decision can be significant, especially if the chosen cable does not enjoy widespread support in the future.Previous research has raised the possibility that cable selection is not necessarily a well-reasoned decision in many cases. Decisions may be based on little analysis, and decision makers may be influenced by those not motivated by the organisation's best interests (Dell, 2005).Part of a larger research project spanning Australia, China, and south-east Asia, this study investigates current trends in structured cable infrastructure in Australia. Results suggest that many of the "textbook" reasons for adopting different transmission media are often not considered.